The influence of unbalanced magnetic pull on the reliability of induction motors - Israel David Braude (Department of Electrical Engineering, 2024)
This thesis is a study of the influence of unbalanced magnetic pull (~.m.p.) and associated phenomena on the reliability of induction motors. The work arose from investigations into the premature failure or malfunction of several large and important 6600 volt induction motors whilst in service. Insofar as the writer can determine much of the work reported iii in this thesis constitutes a new contribution to the experimental and theoretical knowledge of induction motors. This applies particularly to the experimental observations on large 4-pole induction motors, to the theoretical analysis and discussions and to the development of detailed enquiry documents and associated documents which include all the principal factors involved in the selection of 6600 volt induction motors. The success of the writer's approach has been shown by the outstanding performance and perfect reliability in service of all the motors selected on this basis. This supports the writer's thesis that the effects of the radial electromagnetic forces, including the unbalanced magnetic pull due to airgap eccentricity must be carefully taken into account in the design and construction of induction motors in order to achieve high reliability. The following preface provides an expanded abstract of this work.